Usefulness of the human papillomavirus DNA chip test as a complementary method for cervical cytology - Lee, Rae-Young; Koo, Joo-Yeon; Kim, Nah-Ihm; Kim, Sung-Sun; Nam, Jong-Hee; Choi, Yoo-Duk (CytoJournal, 2023)
As a convenient and economical method of screening cervical cancer and precancerous pathologies, the Papanicolaou smear (Pap smear) has been most widely used. Nevertheless, it requires cytological changes for making diagnoses and reportedly has a high false-negative rate. In this study, the usefulness of the human papillomavirus (HPV) DNA chip test as a complementary method that can compensate for the defect of the Pap smear was investigated.ObjectivesAs a convenient and economical method of screening cervical cancer and precancerous pathologies, the Papanicolaou smear (Pap smear) has been most widely used. Nevertheless, it requires cytological changes for making diagnoses and reportedly has a high false-negative rate. In this study, the usefulness of the human papillomavirus (HPV) DNA chip test as a complementary method that can compensate for the defect of the Pap smear was investigated.Of the 6516 patients who simultaneously underwent a Pap smear and an HPV DNA chip test at Chonnam National University Hospital between January 2015 and December 2016, 1897, an initial PAP smear-negative patients who had undergone an additional Pap smear during their 2-year follow-up period were selected for this study. Of the subject patients, 281 underwent a cervical biopsy.Material and MethodsOf the 6516 patients who simultaneously underwent a Pap smear and an HPV DNA chip test at Chonnam National University Hospital between January 2015 and December 2016, 1897, an initial PAP smear-negative patients who had undergone an additional Pap smear during their 2-year follow-up period were selected for this study. Of the subject patients, 281 underwent a cervical biopsy.The Pap smear follow-up of an initial Pap smear-negative subjects showed 53 (75.7%) HPV high-risk positive cases in the cytology low-grade lesion group (70 cases) and 46 (97.8%) HPV high-risk positive cases in the cytology high-grade lesion group (47 cases). The 281 biopsy cases included 67 biopsy low-grade lesion cases and 74 biopsy high-grade lesion cases, of which there were 45 (67.2%) and 67 (90.5%) HPV high-risk positive cases, respectively. The follow-up cytology on the high-risk HPV-positive subjects showed that the ratio of their high-grade lesions was 260.8 times greater than that of the high-risk HPV-negative subjects (OR = 260.8 and 95% CI: 36.1 and 1886.1); and their biopsy showed that the ratio of their high-grade lesions was 102.7 times greater than that of the HPV-negative subjects (OR = 102.7 and 95% CI: 14.0 and 753.3).ResultsThe Pap smear follow-up of an initial Pap smear-negative subjects showed 53 (75.7%) HPV high-risk positive cases in the cytology low-grade lesion group (70 cases) and 46 (97.8%) HPV high-risk positive cases in the cytology high-grade lesion group (47 cases). The 281 biopsy cases included 67 biopsy low-grade lesion cases and 74 biopsy high-grade lesion cases, of which there were 45 (67.2%) and 67 (90.5%) HPV high-risk positive cases, respectively. The follow-up cytology on the high-risk HPV-positive subjects showed that the ratio of their high-grade lesions was 260.8 times greater than that of the high-risk HPV-negative subjects (OR = 260.8 and 95% CI: 36.1 and 1886.1); and their biopsy showed that the ratio of their high-grade lesions was 102.7 times greater than that of the HPV-negative subjects (OR = 102.7 and 95% CI: 14.0 and 753.3).The complementary use of the HPV DNA chip test may be useful in increasing the accuracy of screening examinations for the early diagnosis of uterine cervix cancer when combined with the Pap smear.ConclusionThe complementary use of the HPV DNA chip test may be useful in increasing the accuracy of screening examinations for the early diagnosis of uterine cervix cancer when combined with the Pap smear.